Stages of pregnancy and HIV affect diagnosis of tuberculosis infection and Mycobacterium tuberculosis (MTB)-induced immune response: Findings from PRACHITi, a cohort study in Pune, India - Ramesh Bhosale (Elsevier, 2021)
Background: Accurate tuberculosis infection (TBI) tests are critical for pregnant women, especially those with HIV, who have a high risk of TB disease. Methods: We enrolled interferon gamma release assay (IGRA)+ pregnant women with and without HIV in a longitudinal study, followed up at delivery and 6 months postpartum. Tuberculin skin test (TST) and IGRA were compared by HIV status at each timepoint. Results: Of 165 enrolled IGRA+ pregnant women: 35 (21%) had HIV and were on antiretroviral therapy with median CD4 of 476 (IQR 399–586). Compared to antepartum, significantly fewer women remained IGRA+ at delivery [HIV+ n=21/35 (62%, p=0.009); HIV- n=100/130 (77%, p=0.002)] and postpartum [HIV+ n=30/35 (87%, p=0.03); HIV– n=116/130 (89%, p=0.01)]. IGRA/TST discordance was high in pregnant women (HIV+: 51%; HIV-: 25%). Median IFN-γ was lowest for all women at delivery; significantly lower in women with HIV at all timepoints compared to women without HIV. TB incidence was 50/ 1000 person-years and 18/1000 person-years among women with and without HIV respectively. Conclusions: Pregnancy affects TBI test results and reduces IFN-γ response to M. tuberculosis stimulation. Despite adequate CD4 counts, women with HIV express less IFN-γ than women without HIV, which may explain the high TB incidence in postpartum women with HIV.